Manejo De Los Ingresos De Automotriz “Mora” - Contreras Caregua, Natali Juleydi (2017)
The present work is focused on generating knowledge about the income management of the Mora Automotriz, which requires improving its financial and accounting system, as well as transactions or operations, since it is important to have an adequate revenue record for the appropriate decision-making within the establishment. In a business environment where there are continuous changes in the technology, the success that the company can have depends on the correct decisions that the managers take for the correct registration of generated sales and the expenses that have incurred to generate the profits and that personal is adequately trained within the institution. Within this research the main objective is to know the procedures that the company must execute in order to obtain higher revenues, for this it is necessary to make a revision to the sales revenue made in order to determine the registration of the existing sales and if they were registered in the dates which were carried out.